Intradural lumbar disc herniation: report of five cases with literature review - Ducati, Luis Gustavo [UNESP]; Silva, Mateus Violin; Brandão, Michele Madeira; Romero, Flavio Ramalho [UNESP]; Zanini, Marco Antonio [UNESP] (Springer Nature, 2012)
Introduction: Intradural lumbar disc herniations are uncommon presentations of a relatively frequent pathology, representing less than 1% of all lumbar disc hernias. They show specific features concerning their clinical diagnosis, with a higher incidence of cauda equina syndrome, and their surgical treatment requires a transdural approach. Methods: In this article, we describe five cases of this pathology and review the literature as well as some considerations about the difficulties in the preoperative diagnostic issues and the surgical technique. Conclusion: We concluded that for intradural disc herniations the diagnosis is mainly intraoperative, and the surgical technique has some special aspects. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Cauda equina syndrome; Intradural herniation; Lumbar herniated disc; Microdiscectomy